Pro impetrandis pecuniis. Nine lists of lenders in Milan (1451) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
Nine lists of 220 potential lenders of money compiled in 1451 by the agents of Francesco Sforza, the new duke of Milan, are edited here, together with short bio graphical notes. An introduction explains the possible criteria of the choice. The first criterion was wealth, since many of them belonged to the medium-high level of the Milanese merchants and businessmen’s class. Another criterion was related to politics: most of the lenders were deeply compromised with the experience of the Repubblica Ambrosiana (1447-1450). Therefore, the forced loans may also be considered a measure provided by the Duchy against internal political dissidence.DOI 10.17464/9788867742738
Keywords: Duchy of Milan; 15th century; milanese merchants and businessmen; Repubblica Ambrosiana